LIM Homeobox 4 (lhx4) regulates retinal neural differentiation and visual function in zebrafish - Rui Guo (Nature Portfolio, 2021)
Abstract LIM homeobox 4 (LHX4) is expressed in the photoreceptors (PRs) of the outer nuclear layer (ONL) and bipolar cells (BCs) of the inner nuclear layer (INL) in mouse and chicken retina. It regulates the subtype-specific development of rod BCs and cone BCs in the mouse retina. However, no report has been published on its expression and function in the zebrafish retina. In this study, we assessed the expression of Lhx4 using in situ hybridization (ISH) technique and explored its role in zebrafish (Danio rerio) retinal development via morpholino (MO) technology. We found that the expression of lhx4 in the zebrafish retina begins 48 h post-fertilization (hpf) and is continuously expressed in the ONL and INL. A zebrafish model constructed with lhx4 knockdown in the eyes through vivo-MO revealed that: lhx4 knockdown inhibits the differentiation of Parvalbumin+ amacrine cells (ACs) and Rhodopsin+ rod photoreceptors (RPs), enhances the expression of visual system homeobox 2 (vsx2); and damages the responses of zebrafish to light stimulus, without affecting the differentiation of OFF-BCs and rod BCs, and apoptosis in the retina. These findings reveal that lhx4 regulates neural differentiation in the retina and visual function during zebrafish embryonic development.